Properties of Mechanochemically Synthesized Famatinite Cu3SbS4 Nanocrystals - Erika Dutková; Jaroslav Kováč; Jaroslav Kováč; Jiří Hejtmánek; Petr Levinský; Adelia Kashimbetova; María Jesús Sayagués; Martin Fabián; Zdenka Lukáčová Bujňáková; Matej Baláž; Katarína Gáborová; Viktor Puchý; et al. (Micro, 2023)
In this study, we report the optoelectric and thermoelectric properties of famatinite Cu3SbS4 that was mechanochemically synthesized in a planetary mill from powder elements for 120 min in an inert atmosphere. The tetragonal famatinite Cu3SbS4 was nanocrystalline with a crystallite size of 14 nm, as endorsed by Rietveld refinement. High-resolution transmission electron microscopy showed several crystallites in the range of 20–50 nm. Raman spectroscopy proved the purity of the synthesized famatinite Cu3SbS4 and chemical-state characterization performed by X-ray photoelectron spectroscopy confirmed that the prepared sample was pure. The Cu1+, Sb5+, and S2− oxidation states in Cu3SbS4 sample were approved. The morphology characterization showed homogeneity of the prepared sample. The photoresponse of Cu3SbS4 was confirmed from I–V measurements in the dark and under illumination. The photocurrent increase reached 20% compared to the current in the dark at a voltage of 5 V. The achieved results confirm that synthesized famatinite Cu3SbS4 can be applied as a suitable absorbent material in solar cells. The performed thermoelectric measurements revealed a figure of merit ZT of 0.05 at 600 K.